Performance Of The Lamangga Village Government In Murhum Sub-District, Baubau City In Achieving The Land And Building Tax Target (PBB-P2) - Farliany Hasinu Daa; La Ode Syaiful Islamy H; Zainul Abidin (Sean Institute, 2024)
This study aims to explain the performance of the Lamangga Village Government in achieving the target of urban and rural land and building tax (PBB-P2). This research uses a descriptive method with a qualitative approach. Data sources are primary data and secondary data, Data is collected using interview techniques, observation and documentation. Data techniques were analysed by preparing data and organising data, reducing data and presenting data. The results showed that the performance of the Lamangga Village Government in achieving the Urban and Rural Land and Building Tax (PBB-P2) target was adequate in terms of responsiveness, productivity, accountability, quality, use of resources and costs. The responsiveness of the Lamangga Village government is good in terms of responding to the hopes and aspirations of the community. Responsiveness is done through socialisation, education, solution finding and facilitation related to PBB-P2 billing and payment. Productivity in achieving PBB-P2 targets can be said to be good. Although currently it has not reached 100% of the target and has not been very effective, there have been real and directed steps to achieve these conditions. Regarding accountability, the Lamangga Village Government follows the rules in collecting taxes. Referring to Baubau City Regional Regulation No. 7 of 2013 and the Mayor's Decree on PBB-P2 collection collectors in Baubau City. Although there is actually a new regulation of the HKPD Law number 1 of 2022, it has not been followed by a new regional regulation. The quality of the Lamangga Village government to fulfil the PBB target can be said to be adequate, because the Lamangga Village Government in serving the community does not discriminate, always fast and precise. The use of resources is well organised from planning to implementation of levies. The resources used, such as staff, collectors and RT and RW heads, are very instrumental and helpful. Honorarium and facility fees are paid by the city government through the Budget Implementation List at Baubau City Bapenda.